Are Teacher Ethics Really Complicated? Attempting an Uncomplicated Appraisal... - Mishra, Preeti Vivek (Voices of Teachers and Teacher Educators, 2019)
The paper engages with the issue of teacher ethics while adopting an experiential-investigative tone as a practicing teacher-educator. It draws upon the existing literature to establish the near ubiquity of positing teaching as an ethical enterprise. However by drawing upon, as an illustrative case in point, the author’s recent intellectual run-ins with a promising and critical B.Ed. student, the author attempts to highlight how this ubiquity gets undermined, restricted and challenged in the wake of inter alia institutional collegiality. The paper raises questions on the ethicality of attempting a balancing act among the established taxonomies of ethics and whether a vision of uncompromising ethics in teaching qualify as utopia or are par for course.